How Housing Stress Affect Health Care Costs: A Panel Data Study - Gai Liu PhD; Jianchao Zhou PhD; Yuxiang Wang MD (SAGE Publishing, 2024)
As housing prices in China continue to escalate and the limitations of the "personal unlimited liability system" for housing loans become more evident, the financial stress on families has significantly increased. This stress not only impacts the physical and mental health of family members but also results in rising health care costs. This paper presents empirical research examining how housing stress influences changes in household health care costs through a panel data analysis. The study is based on the China Family Panel Study (CFPS) database and employs a panel two-way fixed effect model alongside a mediating effect model to examine the impact of housing stress, family income, and health status on health care costs. The findings reveal a significant positive correlation between housing stress and health care costs; specifically, for every 1% point increase in housing stress, health care costs rise by 0.141. Robustness tests and propensity score matching (PSM) further validate these findings, even after addressing endogeneity issues. Mediation effect analysis indicates that for every 1% point increase in housing stress, household disposable income decreases by 1.749, and health status declines by 0.468, thereby increasing household health care costs. Heterogeneity analysis demonstrates that housing stress has a more pronounced impact on health care costs among western, eastern, urban, and rental households. The government should implement various measures, such as promoting a "personal limited liability system" mortgage policy, reducing housing prices, and ensuring equal rights to rent and purchase, to alleviate housing stress, enhance family income, and improve residents' health status. These actions would contribute to the promotion of both the housing market and medical care, supporting the sustainable development of the health care sector and ultimately improving long-term social welfare.